(3eYQaI Ydhe GdMOjK hCfhGYgs - (3GdMGce GdfjSGHhQj , eMeO Hf YHO Gddg Hf MeOhjg Hf fYje GdVHj GdWgeGfj GdfjSGHhQj, CHh YHO Gddg, GdMGce, GHf GdHjY,J (B405 (3g` s
(3ChdgG (B:s
(3CeG HYO aEfi deG QCjJ GdHOY ai ReGffG cKQJ heYQaI GdfGS HCUhd GdSff bdJ OYGfi Pdc Edi JUfja cJGH Naja GTJed Ydi PcQ CfhGY Yde GdMOjK s
(3BNQgG (B:s
(3eYc cJGH HMjQ ai SYO gPG BNQ cJGH GdeYQaI s
(3GdfSNI HgG MhGTs
(3QhGjI CHh HcQ Hf CHj GdMSf Hf Nda GdTjQGRis
(3SeGY YHO Gddg Hf CMeO Hf YeQ GdSeQbfOis
(3fSNI KGfjI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B227 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B10 - (3U (B238s
Keywords: (3GdMOjK h GdeUWdMs